Fast and Easy Nanopore Sequencing Workflow for Rapid Genetic Testing of Familial Hypercholesterolemia - Soufi, Muhidien; Bedenbender, Simon; Ruppert, Volker; Kurt, Bilgen; Schieffer, Bernhard; Schaefer, Juergen R. (Frontiers in Genetics, 2022)
Familial hypercholesterolemia (FH) is an autosomal dominant lipid metabolism disorder characterized by severely elevated plasma low-density lipoprotein cholesterol levels. The disease is caused by mutations in 3 genes (LDLR, APOB and PCSK9) while over 90 % of the mutations are located within the LDLR gene. Thus, genetic analysis of the LDLR gene is the first step in the genetic diagnosis of FH. However, conventional methods like Sanger and NextGen sequencing are still costly and time-consuming. In contrast, Oxford Nanopore technology sequencing is an emerging third-generation sequencing technology featured by easy operability, low cost, small size and the capability of parallel sample sequencing. Here, we present an easy Nanopore-sequencing-based workflow for the rapid genetic testing of FH taking only 3 days and costing less than $50 per sample without the requirement for deep bioinformatic knowledge. Using our workflow, we were able to identify the underlying mutations of 10 FH patients including one novel, not yet recorded mutation. Our workflow allows the rapid evaluation of the mutations by utilizing detailed variant information from Ensembl. Additionally, our workflow is not restricted to sequencing the LDLR gene alone but can be easily adapted to the other FH-causing genes and more importantly, to any desired gene contributing to any hereditary disease. Therefore, our workflow is an attractive opportunity for every diagnostic laboratory to offer fast and easy in-house genetic diagnostics.